FORTIFICATION OF GEMBILI FLOUR (Dioscorea esculenta) IN THE COB- SPEED LOAD NUGGETS KNOW AS INULIN SOURCE - Mikchaell A.P Panjaitan; Titik Dwi Sulistiati (Journal of Aquaculture Development and Environment, 2020)
Gembili (Dioscorea esculenta) is a plant that contains high inulin. Inulin is a type of carbohydrate that contains fiber and is classified as a prebiotic. Inulin will still undergo fermentation even by the good microbes present in the large intestine so that it has positive implications for the diets of people with diabetes. This study aims to determine the effect of fortification of gembili flour (Dioscorea esculenta) on the physical, chemical, and organoleptic characteristics of tongkol-dregs tofu pindang nuggets. The method used in this research is the experimental method. The experimental design in the main study was a simple completely randomized design (CRD) using 4 replications. The independent variable used in this study is the difference in the concentration of gembili flour in the manufacture of tuna-tofu tuna pindang nuggets. While the dependent variable in this study is the content of food fiber nuggets of tuna-tofu. The results of this study indicate that the substitution of gembili flour with different concentrations has a significant effect on the inulin content of tongkol-tofu tuna nuggets. However, there is no significant effect on the physical characteristics, namely texture and organoleptics, which include the appearance, aroma, taste and texture of the tuna-tofu tuna nuggets.